2015
DOI: 10.1007/s00280-015-2807-7
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab in combination with docetaxel/cisplatin/S-1 (DCS) for patients with HER2-positive metastatic gastric cancer: feasibility and preliminary efficacy

Abstract: UMIN000005603.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…In addition, no cases of cardiac failure or mortality due to cardiac toxicity were observed. Similarly, previous reports have shown that adding trastuzumab to chemotherapy does not increase the toxic effects associated with standard fluoropyrimidine and platinum chemotherapy (4,(16)(17)(18)(19). The toxicity profile of trastuzumab plus chemotherapy has been shown to be comparable to that for chemotherapy alone in phase II and III trials (4,20,21).…”
Section: No Patients -----------------------------------------------mentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, no cases of cardiac failure or mortality due to cardiac toxicity were observed. Similarly, previous reports have shown that adding trastuzumab to chemotherapy does not increase the toxic effects associated with standard fluoropyrimidine and platinum chemotherapy (4,(16)(17)(18)(19). The toxicity profile of trastuzumab plus chemotherapy has been shown to be comparable to that for chemotherapy alone in phase II and III trials (4,20,21).…”
Section: No Patients -----------------------------------------------mentioning
confidence: 84%
“…High efficacy of trastuzumab has been confirmed prior to and following chemotherapy in patients with HER2-positive breast cancer, and expanded indications in gastric cancer are anticipated (14,15). Previous studies that have assessed chemotherapy plus trastuzumab treatment regimens for patients with HER2-positive gastric cancer have revealed good tolerance and high efficacy with cytotoxic chemotherapy including S-1 plus cisplatin, capecitabine plus oxaliplatin (or docetaxel), and cisplatin plus S-1, however, not capecitabine plus cisplatin (16)(17)(18)(19)(20)(21). Therefore, trastuzumab with cytotoxic chemotherapy is considered a standard treatment regimen for patients with HER2-positive gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 25% of all female breast cancers exhibit an over-expression of HER2, which is known to drive aggressive cellular behavior[37]. Trastuzumab (a monoclonal antibody), the first-line of treatment for HER2+ breast cancers[810], has been shown to be active as a single agent[11,12] as well as in combination with chemotherapy[9,10,13] for the treatment of advanced stage HER2+ breast cancer. Its use has been shown to positively affect patient outcomes such as progression-free survival (PFS) and overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…In total, 15 studies containing 557 patients were included, investigating nine alternative backbone regimens ( Table 1). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The ToGA trial included 228 patients in the trastuzumab plus cisplatin and capecitabine/5-FU arm. In the doublet and triplet backbone studies, no major differences in patient population were observed compared to the ToGA population (Table 1).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%